2014
DOI: 10.1123/ijspp.2013-0187
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Accelerations With GPS in Football: Time to Slow Down?

Abstract: The aims of the current study were to examine the magnitude of between-GPS-models differences in commonly reported running-based measures in football, examine between-units variability, and assess the effect of software updates on these measures. Fifty identical-brand GPS units (15 SPI-proX and 35 SPIproX2, 15 Hz, GPSports, Canberra, Australia) were attached to a custom-made plastic sled towed by a player performing simulated match running activities. GPS data collected during training sessions over 4 wk from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
159
3
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(184 citation statements)
references
References 6 publications
2
159
3
9
Order By: Relevance
“…However, this variable was intended to represent the overall acceleration and deceleration load imposed on the athlete, rather than an estimate of energy consumption. Recent research has demonstrated that GPS possess poor inter-unit reliability for both acceleration counts >3 m·s -2 and >4 m·s -2 (CV% = 31% and 43%, respectively), and deceleration counts <-3 m·s -2 and <-4 m·s -2 (CV% = 42% and 56%, respectively) 15 . However, in the present study, each player was assigned the same unit for each match, and this coupled with the 'smoothing' effect of the moving average method, may have provided a more stable measure for differentiating demands between positions and durations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this variable was intended to represent the overall acceleration and deceleration load imposed on the athlete, rather than an estimate of energy consumption. Recent research has demonstrated that GPS possess poor inter-unit reliability for both acceleration counts >3 m·s -2 and >4 m·s -2 (CV% = 31% and 43%, respectively), and deceleration counts <-3 m·s -2 and <-4 m·s -2 (CV% = 42% and 56%, respectively) 15 . However, in the present study, each player was assigned the same unit for each match, and this coupled with the 'smoothing' effect of the moving average method, may have provided a more stable measure for differentiating demands between positions and durations.…”
Section: Discussionmentioning
confidence: 99%
“…The number of satellites and HDOP during match play were 8.3 ± 1.4 and 1.1 ± 0.1, respectively. Whilst the validity and reliability of GPS for measures of total distance have been established 13,14 , the inter-unit reliability of GPS for assessing accelerations during team sport movements has been questioned 15 . To account for this issue, each player wore the same unit for the entire study.…”
Section: Methodsmentioning
confidence: 99%
“…Only recently, however, several studies have described the in-season training periodization practices of elite football teams in detail, including a comparison of training days within weekly micro-cycles (Akenhead, Harley, & Tweddle, 2016;Malone et al 2015;Anderson et al 2016). Malone et al (2015) found that only the last training before the match differed from the other training days on several internal and external load variables, but they did not include accelerations and metabolic power estimations because the accuracy of GPS measurements of high-intensity velocity changes is limited (Akenhead et al 2014;Buchheit et al 2014a). Nevertheless, Akenhead et al (2016) used GPS and reported that when the training session was closer to match day distance ran while accelerating and decelerating followed a similar decrease as total distance and distance ran at high speeds.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizou-se sistema de posicionamento global (GPS) individual, modelo SPI-Pro X2 (GPSports, SPI-Pro X, Canberra, Austrália), que apresenta um acelerômetro triaxial de 100Hz e monitora distâncias e posições a uma frequência de 15Hz, apresentando suficiente acurácia para ações de aceleração e distância percorrida no futebol 26 . O dispositivo de GPS foi fixado junto ao tórax dos atletas por meio de vestimenta específica.…”
Section: Métodosunclassified